Prevalenței tulburărilor musculo-scheletale în rândul studenților de medicină dentară - Carina Balcoș; Magda Bârlean; Livia Bobu; Lucia Bârlean (Romanian Dental Association for Education, 2018)
Musculoskeletal disorders (MSD) are common among dental practitioners. The aim of the study was to assess the prevalence of MSD among dental students as well as the level of knowledge and attitudes about the principles of ergonomics. Material and Methods: The study was conducted among the 2nd and 6th year students of the Faculty of Dental Medicine, UMPh Gr.T.Popa University of Iasi. The questionnaire covered four main sections: the first section on demographic data collection, the second section assessed the work environment and work characteristics, the third section addressed ergonomics, while the fourth section assessed the prevalence of MSD based on body regions. Data analysis was performed with SPSS 14.0 Results: The response rate was 87% .72% of female subjects and 20% of male subjects reported MSD symptoms. 50% of students work with an assistant. They reported few symptoms of MSD at the elbow and forearm level. 70% of students have the ability to take over the instrument without making unnecessary movement. The number of clinical weekly workouts was significantly correlated with the discomfort experienced in the hands and fingers but also with the pain in the lumbar region. Conclusions: The prevalence of musculoskeletal disorders is higher in end-year students. The causes of these illnesses are the low level of knowledge about the ergonomic principles that need to be applied to improve medical activity and the reduction of the risk of installing muscle fatigue but also the lack of auxiliary staff to help the student achieve the treatments.